The 3' untranslated region of the hsp 70 genes maintains the level of steady state mRNA in Trypanosoma brucei upon heat shock. - Lee, M G (1998)
An increase in the transcriptional efficiency at elevated temperatures is a characteristic of transcription of heat shock protein (hsp) coding genes in most eukaryotes analyzed to date. The regulatory mechanism for hsp 70 genes expression in Trypanosoma brucei does not follow the conventional transcriptional induction mechanism. The hsp 70 locus of T.brucei appears in a permanently activated state, and transcriptional induction of hsp 70 genes by heat shock does not occur in this organism. Therefore, the differential expression of the hsp 70 genes in trypanosomes is, to a large extent, post-transcriptionally controlled. Mechanisms of post-transcriptional control of the hsp 70 gene expression were investigated. Procyclic trypanosomes were normally maintained at approximately 25 degreesC. Incubation of procyclic trypanosomes at 41 degreesC drastically reduced the steady state mRNA levels of many protein coding genes. In contrast, the expression of the hsp 70 genes is either maintained at a high level or is up-regulated. The hsp 70 intergenic region promoter together with its 3' splice acceptor sites and the 5' untranslated region (UTR) are not sufficient to maintain or up-regulate the mRNA level of a reporter gene upon heat shock. However, addition of the 3' UTR of hsp 70 genes to a reporter gene, driven by different promoters, maintained a high level expression of the mRNA during heat shock. These results suggested that the 3' UTR of the hsp 70 genes is primarily responsible for the maintenance of mRNA level during heat shock, while mRNA containing the 3' UTR from many other genes may be rapidly degraded by heat shock induced processes.